2/3x-1/6=5/x-2/3

Simple and best practice solution for 2/3x-1/6=5/x-2/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2/3x-1/6=5/x-2/3 equation:


D( x )

x = 0

x = 0

x = 0

x in (-oo:0) U (0:+oo)

(2/3)*x-(1/6) = 5/x-(2/3) // - 5/x-(2/3)

(2/3)*x-(5/x)-(1/6)+2/3 = 0

(2/3)*x-5*x^-1-1/6+2/3 = 0

2/3*x^1-5*x^-1+1/2*x^0 = 0

(2/3*x^2+1/2*x^1-5*x^0)/(x^1) = 0 // * x^2

x^1*(2/3*x^2+1/2*x^1-5*x^0) = 0

x^1

(2/3)*x^2+(1/2)*x-5 = 0

(2/3)*x^2+(1/2)*x-5 = 0

DELTA = (1/2)^2-(-5*4*(2/3))

DELTA = 163/12

DELTA > 0

x = ((163/12)^(1/2)-(1/2))/(2*(2/3)) or x = (-(1/2)-(163/12)^(1/2))/(2*(2/3))

x = 3/4*((163/12)^(1/2)-1/2) or x = -3/4*((163/12)^(1/2)+1/2)

x in { -3/4*((163/12)^(1/2)+1/2), 3/4*((163/12)^(1/2)-1/2)}

x in { -3/4*((163/12)^(1/2)+1/2), 3/4*((163/12)^(1/2)-1/2) }

See similar equations:

| 2x-(3x-3)=3x-5 | | 3H+2C=5.45 | | x(x+3)=11 | | 9-4m=2m-3 | | Y=2(0+3)(0-4) | | 4y-23=10+y | | 23+13x-15+5x-27x= | | 14000V=-2000t+20000 | | 5(9a)= | | 14000V=-2000+20000 | | -10x+14-8x+9= | | 3x-4(1-2x)=2x-(x+1) | | 2(a-b)= | | 3.7(-83x+-3)=3.7(7x+-30) | | (2x-1/2)^2=9/4 | | X+2x+4x+2=37 | | (13-6)x(12-3)+16= | | 3a^2+25+42=0 | | 9n=6 | | -49=.7y | | 2[5(4-1)]= | | x-4=169 | | t^2-19t+10=0 | | x^2y^2-2y=0 | | in(2x)-in(3x+2)=1 | | -8(w-3)=9w+41 | | (7x-9)(9x+9)=0 | | (49-12)/3 | | (2x-7)(9x+8)=0 | | 17=85 | | 17Xa=85 | | x+25=51 |

Equations solver categories